Transcriptomic features of immune inflammation and neural plasticity associated with early neurological improvement in acute ischemic stroke patients with large vessel occlusion - Dong Zhang; Xinying Jing; Ruinan Ma; Zhizhang Li; Xiaoguang Zhang; Ying Ding; Yunhua Yue (Frontiers in Neuroscience)
BackgroundAcute ischemic stroke (AIS) caused by large vessel occlusion (LVO) is a leading cause of disability and mortality worldwide. Although endovascular thrombectomy (EVT) has significantly improved outcomes, many patients do not achieve early neurological improvement (ENI) despite timely reperfusion. This study aims to investigate the peripheral blood mRNA molecular characteristics and underlying mechanisms associated with ENI after EVT in AIS-LVO patients, to inform individualized treatment and optimize prognosis.MethodsThis retrospective study included AIS-LVO patients who underwent EVT between January 2022 and December 2023. Peripheral blood samples were collected before reperfusion therapy for mRNA transcriptome sequencing and bioinformatic analysis. Patients were grouped according to ENI status. Differentially expressed genes (DEGs) were identified, and functional enrichment, signaling pathway, and protein-protein interaction network analyses were performed.ResultsA total of 108 patients were initially screened, and 20 were ultimately included in the study (13 in the ENI group and 7 in the non-ENI group). Among the 20,501 genes detected, 752 were found to be significantly differentially expressed, with 208 upregulated and 544 downregulated. The upregulated genes in the ENI group were mainly enriched in immune and inflammatory response pathways, such as NOD-like receptor and Toll-like receptor signaling. In contrast, the downregulated genes were primarily associated with neurodevelopment and synaptic plasticity. Protein-protein interaction analysis identified immune-related genes, including JUN, IL1A, and CCR5, as central nodes. Overall, the ENI group exhibited a dynamic balance between immune activation and suppression of neuronal plasticity.ConclusionThis study reveals the transcriptomic characteristics of ENI in AIS-LVO patients during the acute phase, highlighting the protective roles of moderate immune-inflammatory activation and suppression of neural plasticity in acute injury response. The identification of related molecular pathways and biomarkers provides a theoretical basis for individualized treatment and improved functional outcomes. Future studies should expand sample size and integrate single-cell sequencing and liquid biopsy multi-omics approaches to further clarify the molecular mechanisms of ENI and promote clinical translation.